Human Rights Problem of Stranded Refugees in A Transit Country: Case Study in Makassar City, Indonesia - Finahliyah Hasan (Universitas Bosowa, 2018)
Global forced displacement mostly by conflict and persecution continues to escalate dramatically at the end of 2016 and has never been higher since World War II. People fleeing war or another catastrophe who cannot return to their country of origin have been granted asylum in the foreign country. They will be processed to have their claims for refugee status thoroughly assessed by UNHCR in which is named after as a Refugee Status Determination (RSD), a legal process by government or UNHCR to determine whether a person seeking international protection is considered a refugee under international, regional or national law. In fact, the vast majority of refugees who intend to migrate to developed states as their final destination, generally settle first in a stable and middleincome country such as Indonesia. As a result, Indonesia is swamped by refugees, and their condition has been exacerbated by Indonesia status which is not the signatory of the 1951 Refugee Convention. This status leads to the limitation for accessing human rights of refugees. Thus fulfilling refugee's rights are prevalent due to the uncertainty for resettlement to the third country. Notwithstanding some institutions such as International Organization for Migration (IOM), Immigration, and Social Service department have conducted programs for a refugee to overcome their lack of activities, the implementation is uneven. The findings of this research demonstrates that (1) when refugees are not permitted to get a job, have limited access to education and affordable health facilities, (2) The program sufferes from various difficulties due to the lack of cooperation with related agencies and the lack of human resources, they continue to suffer with their refugee status being negatively affected. This study used a participatory method, observation and literature review. Data is obtained through the interview of refugees and related authorities in different locations. During collecting the data, the author implemented several empowerment programs in refugee community housing as a strategy of the author who encounters difficulties while getting information.